Charging roll for electro-photographic apparatus
Patent Information
- Application Number
- JP2022101690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-06-24
AI Technical Summary
Charging rolls in electrophotographic equipment experience increased resistance and ion conductive agent bleeding due to polarization and concentration issues, leading to image defects.
A charging roll with an elastic layer composed of a crosslinked rubber composition containing hydrin rubber, nitrile rubber, crosslinking agents, ionic conductive agents, piperidinyloxy radical compounds, and salts of cyclic amidine or thiophthalimide compounds, which suppress excessive polarization and bleeding.
The solution effectively maintains low resistance and prevents ion conductive agent bleeding during energization durability, ensuring consistent performance and image quality.
Smart Images

Figure 00000000_0000_ABST 
Figure 00000000_0001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a charging roll for electrophotographic equipment, which is suitably used in electrophotographic equipment such as copying machines, printers, and facsimiles that employ an electrophotographic system. [Background technology]
[0002] An ion conductive mechanism is sometimes required for the charging roll of an electrophotographic device for the purpose of electrical uniformity, etc. For example, Patent Document 1 discloses that an ion conductive agent is blended in the base layer of the charging roll. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-132020 A Summary of the Invention [Problem to be solved by the invention]
[0004] If the charging roll continues to be subjected to an electrical load by passing electricity through it, the electrical resistance of the charging roll increases, and there is a risk of image damage due to a decrease in charging ability. This is because when an electrical load is applied to the charging roll, the ionic conductive agent in the base rubber layer of the charging roll is polarized, and the polarization of the ionic conductive agent is too fast, causing the polarized anions and cations to be excessively biased toward the + electrode and - electrode sides, respectively, resulting in less ionic conductive agent in the center of the base rubber layer and creating areas with high electrical resistance. If the amount of ionic conductive agent is excessively increased in order to suppress the excessive polarization in the base rubber layer, this can lead to bleeding of the ionic conductive agent, which can cause image damage.
[0005] An object of the present invention is to provide a charging roll for an electrophotographic device, which is capable of suppressing an increase in resistance during long-term energization and bleeding of an ion conductive agent. [Means for solving the problem]
[0006] The charging roll for an electrophotographic device according to the present invention comprises a shaft body and an elastic layer formed on the outer peripheral surface of the shaft body, and the elastic layer is a crosslinked body of a rubber composition containing the following (a) to (e): (a) One or more types selected from hydrin rubber and nitrile rubber (b) Crosslinking agent (c) Ionic Conductive Agent (d) one or more selected from piperidinyloxy radical compounds and phenolic antioxidants (e) one or more compounds selected from salts of cyclic amidine compounds and thiophthalimide compounds
[0007] The (e) may be a naphthoic acid salt of a cyclic amidine compound. The (e) may be N-cyclohexylthiophthalimide. The (c) may be an ammonium, phosphonium, or imidazolium ion conductive agent. The (c) may be an ion conductive agent containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion. The rubber composition may further have a specific surface area of 40 m 2 / g or more 300m 2 It is preferable that the carbon black content be less than or equal to 1 g.
[0008] (1) The charging roll for an electrophotographic device according to the present invention comprises a shaft body and an elastic layer formed on the outer peripheral surface of the shaft body, and the elastic layer is a crosslinked body of a rubber composition containing the following (a) to (e): (a) One or more types selected from hydrin rubber and nitrile rubber (b) Crosslinking agent (c) Ionic Conductive Agent (d) one or more selected from piperidinyloxy radical compounds and phenolic antioxidants (e) one or more compounds selected from salts of cyclic amidine compounds and thiophthalimide compounds
[0009] (2) In the above (1), (e) may be a naphthoate salt of a cyclic amidine compound.
[0010] (3) In the above (1), (e) may be N-cyclohexylthiophthalimide.
[0011] (4) In any one of the above (1) to (3), the (c) may be an ammonium-based, phosphonium-based, or imidazolium-based ion-conducting agent.
[0012] (5) In any one of the above (1) to (4), the (c) may be an ion conductive agent containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion.
[0013] (6) In any one of the above (1) to (5), the rubber composition further has a specific surface area of 40 m 2 / g or more 300m 2 It is preferable that the carbon black content be less than or equal to 1 g. Effect of the Invention
[0014] The electrostatic charge roll for electrophotographic equipment according to the present invention comprises a shaft body and an elastic layer formed on the outer peripheral surface of the shaft body, and the elastic layer is a crosslinked body of a rubber composition containing the above-mentioned (a) to (e), so that an increase in resistance during energization and bleeding of the ionic conductive agent are suppressed.
[0015] When the (e) is a naphthoate salt of a cyclic amidine compound, the effect of suppressing an increase in resistance during durability of energization is particularly excellent.
[0016] Furthermore, when the (e) is N-cyclohexylthiophthalimide, the effect of suppressing an increase in resistance during energization is particularly excellent.
[0017] When the (c) is an ammonium-, phosphonium-, or imidazolium-based ionic conductive agent, the polar group of the rubber component (a) is easily coordinated to the cation of the ionic conductive agent, and excessive polarization of the ionic conductive agent is easily suppressed even during electrical durability, which is particularly effective in suppressing resistance increase during electrical durability. Also, the salt of a cyclic amidine compound or a thiophthalimide compound (e) is easily coordinated to the cation of the ionic conductive agent, and excessive polarization of the ionic conductive agent is easily suppressed even during electrical durability, which is particularly effective in suppressing resistance increase during electrical durability. Also, it is easy to achieve low resistance.
[0018] Ionic conductive agents containing sulfonate anions having fluorine atoms or bis(sulfonyl)imide anions having fluorine atoms contain many fluorine groups in their structure, so that the anions themselves have low basicity and form relatively weak ionic bonds with cations. Therefore, these ionic conductive agents are easily dissociated into ions in the rubber (a), and are easy to achieve low resistance. In addition, all of these anions are hydrophobic and have low hygroscopicity even in high humidity environments. Therefore, they are excellent in the effect of suppressing fluctuations in electrical resistance due to environmental changes. Ionic conductive agents containing perchlorate anions are easy to achieve low resistance.
[0019] The rubber composition further has a specific surface area of 40 m 2 / g or more 300m 2 When the carbon black is contained in an amount of 0.1 to 1.0 g / g or less, the effect of suppressing bleeding of the ion conductive agent is improved. [Brief description of the drawings]
[0020] [Figure 1] 1A is a schematic external view of a charging roll for an electrophotographic device according to one embodiment of the present invention, and FIG. 1B is a cross-sectional view taken along line AA thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The charging roll for electrophotographic equipment according to the present invention (hereinafter, simply referred to as the charging roll) will be described in detail. Fig. 1 is a schematic external view (a) of the charging roll for electrophotographic equipment according to one embodiment of the present invention, and its AA line cross-sectional view (b).
[0022] The electrostatic charge roll 10 comprises a shaft 12, an elastic layer 14 formed on the outer peripheral surface of the shaft 12, and a surface layer 16 formed on the outer peripheral surface of the elastic layer 14. The elastic layer 14 is a layer (base layer) that forms the base of the electrostatic charge roll 10. The surface layer 16 is a layer that appears on the surface of the electrostatic charge roll 10. Note that the electrostatic charge roll of the present invention may have a configuration without a surface layer. In other words, the electrostatic charge roll may comprise a shaft 12 and an elastic layer 14 formed on the outer peripheral surface of the shaft 12, and may not have a surface layer 16 on the outer peripheral surface of the elastic layer 14.
[0023] The shaft body 12 is not particularly limited as long as it is conductive. Specific examples include a core bar made of a solid or hollow body made of a metal such as iron, stainless steel, or aluminum. An adhesive, primer, or the like may be applied to the surface of the shaft body 12 as needed. In other words, the elastic layer 14 may be bonded to the shaft body 12 via an adhesive layer (primer layer). The adhesive, primer, or the like may be made conductive as needed.
[0024] The elastic layer 14 is composed of a crosslinked product of a rubber composition containing the following (a) to (e): (a) One or more types selected from hydrin rubber and nitrile rubber (b) Crosslinking agent (c) Ionic Conductive Agent (d) one or more selected from piperidinyloxy radical compounds and phenolic antioxidants (e) one or more compounds selected from salts of cyclic amidine compounds and thiophthalimide compounds
[0025] Examples of hydrin rubber include epichlorohydrin homopolymer (CO), epichlorohydrin-ethylene oxide binary copolymer (ECO), epichlorohydrin-allyl glycidyl ether binary copolymer (GCO), epichlorohydrin-ethylene oxide-allyl glycidyl ether terpolymer (GECO), etc. Among these, ECO and GECO containing ethylene oxide as a copolymerization component are more preferable in that they are more likely to produce a low resistance body than those not containing ethylene oxide as a copolymerization component. Also, GCO and GECO containing allyl glycidyl ether as a copolymerization component are more preferable in that they are less likely to sag than those not containing allyl glycidyl ether as a copolymerization component because they have double bonds.
[0026] The nitrile rubber is acrylonitrile-butadiene rubber (NBR). Nitrile rubber is softer than hydrin rubber, so the ionic conductive agent is more likely to move in the rubber. Even in this case, the configuration of the present invention suppresses the increase in resistance during the duration of current flow and the bleeding of the ionic conductive agent. In addition, when nitrile rubber is included as (a), it is easy to adjust the hardness of the elastic layer 14.
[0027] The crosslinking agent is not particularly limited. Examples of the crosslinking agent include a sulfur crosslinking agent, a peroxide crosslinking agent, and a dechlorination crosslinking agent. These crosslinking agents may be used alone or in combination of two or more.
[0028] Examples of the sulfur crosslinking agent include powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, insoluble sulfur, sulfur chloride, thiuram-based vulcanization accelerators, and polymeric polysulfides.
[0029] Examples of the peroxide crosslinking agent include peroxyketals, dialkyl peroxides, peroxy esters, ketone peroxides, peroxydicarbonates, diacyl peroxides, and hydroperoxides.
[0030] From the viewpoint of a relatively high decomposition temperature and ease of molding at higher temperatures, the peroxide crosslinking agent preferably has a decomposition temperature of 60° C. or higher and a one-minute half-life temperature of 150° C. or higher in a thermal storage test (BAM type: SADT). More preferably, the one-minute half-life temperature is 160° C. or higher, and even more preferably, the one-minute half-life temperature is 170° C. or higher. On the other hand, from the viewpoint of excellent crosslinking speed, the one-minute half-life temperature is preferably 200° C. or lower. More preferably, the one-minute half-life temperature is 190° C. or lower, and even more preferably, the one-minute half-life temperature is 180° C. or lower.
[0031] Preferred peroxide crosslinking agents include peroxyketals, dialkyl peroxides, peroxyesters, etc. Peroxyketals include 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, n-butyl 4,4-di(tert-butylperoxy)valerate, etc. Dialkyl peroxides include di(2-tert-butylperoxyisopropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, etc. Examples of peroxyesters include tert-butyl peroxybenzoate, tert-hexyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butylperoxy-2-ethylhexyl monocarbonate, tert-butyl peroxylaurate, tert-butylperoxy-3,5,5-trimethylhexanoate, tert-hexylperoxyisopropyl monocarbonate, etc. Among these, di(2-tert-butylperoxyisopropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 1,1-di(tert-butylperoxy)cyclohexane, etc. are preferred from the viewpoints that unreacted components are unlikely to remain and that the boiling point of the decomposition product is relatively low and easy to remove.
[0032] Examples of the dechlorinating crosslinking agent include dithiocarbonate compounds, more specifically, quinoxaline-2,3-dithiocarbonate, 6-methylquinoxaline-2,3-dithiocarbonate, 6-isopropylquinoxaline-2,3-dithiocarbonate, 5,8-dimethylquinoxaline-2,3-dithiocarbonate, etc.
[0033] The amount of the crosslinking agent to be mixed is preferably within a range of 0.1 to 2 parts by mass, more preferably within a range of 0.3 to 1.8 parts by mass, and even more preferably within a range of 0.5 to 1.5 parts by mass, per 100 parts by mass of the (a) specific polar rubber, from the viewpoint of preventing bleeding.
[0034] The content of the peroxide crosslinking agent, calculated as the amount of peroxide raw material, is preferably 6 parts by mass or less per 100 parts by mass of component (a) from the viewpoint of easily achieving a low hardness of the elastic layer 14. More preferably, it is 5 parts by mass or less, and even more preferably, it is 4 parts by mass or less. Furthermore, from the viewpoint of achieving an excellent degree of crosslinking of the rubber and being less prone to sagging, the content is preferably 0.2 parts by mass or more per 100 parts by mass of component (a) from the viewpoint of achieving an excellent degree of crosslinking of the rubber and being less prone to sagging, and so on. More preferably, it is 0.4 parts by mass or more, and even more preferably, it is 0.6 parts by mass or more.
[0035] The ionic conductive agent is not particularly limited. Any agent that is used in the field of electrophotographic equipment may be used. Examples of the ionic conductive agent include quaternary ammonium salts, quaternary phosphonium salts, imidazolium salts, borates, and surfactants. Among these, quaternary ammonium salts, quaternary phosphonium salts, and imidazolium salts are particularly preferred.
[0036] Examples of the cation of the quaternary ammonium salt include those having one or more alkyl or aryl groups having about 1 to 18 carbon atoms (e.g., methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, xylyl, etc.). The alkyl or aryl group of the cation of the quaternary ammonium salt is particularly preferably one having 1 to 10 carbon atoms. Examples of the anion of the quaternary ammonium salt include F- ,Cl - ,Br - ,I - Halogen ions such as ClO4 - , BF4 - , PF6 - , SO4 2- , HSO4 - , C2H5SO4 - , CF3COO - , CF3SO3 - , (CF3SO2)2N - , (CF3CF2SO2)2N - , CF3(CF2)3SO3 - , (CF3SO2)3C - , CF3(CF2)2COO - The anion of the quaternary ammonium salt is ClO4 - , (CF3SO2)2N - , CF3SO3 - etc. are more preferable.
[0037] The cation of the quaternary phosphonium salt may have one or more alkyl or aryl groups having about 1 to 18 carbon atoms (e.g., methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, xylyl, etc.). The alkyl or aryl group of the cation of the quaternary phosphonium salt is particularly preferably one having 1 to 10 carbon atoms. The anion of the quaternary phosphonium salt may be, for example, F - ,Cl - ,Br - ,I - Halogen ions such as ClO4 - , BF4 - , PF6 - , SO4 2- , HSO4 - , C2H5SO4 - , CF3COO - , CF3SO3 - , (CF3SO2)2N - , (CF3CF2SO2)2N - , CF3(CF2)3SO3 - , (CF3SO2)3C -, CF3(CF2)2COO - The anion of the quaternary phosphonium salt is ClO4 - , (CF3SO2)2N - , CF3SO3 - etc. are more preferable.
[0038] Examples of the imidazolium salt include unsubstituted imidazolium salts, 1-alkylimidazolium salts, 3-alkylimidazolium salts, 1,3-dialkylimidazolium salts, and 1,2,3-trialkylimidazolium salts. More specifically, for example, 1-methylimidazolium salt, 1,3-dimethylimidazolium salt, 1,3-diethylimidazolium salt, 1,3-dipropylimidazolium salt, 1,3-dibutylimidazolium salt, 1,3-dicyclohexylimidazolium salt, 1-ethyl-3-methylimidazolium salt, 1-propyl-3-methylimidazolium salt, 1-butyl-3-methylimidazolium salt, 1-hexyl-3-methylimidazolium salt, 1-ethyl-2,3-dimethylimidazolium salt, 1-propyl-2,3-dimethylimidazolium salt, 1-butyl-2,3-dimethylimidazolium salt, etc. can be mentioned. The anion of the imidazolium salt is F - ,Cl - ,Br - ,I - Halogen ions such as ClO4 - , BF4 - , PF6 - , SO4 2- , HSO4 - , C2H5SO4 - , CF3COO - , CF3SO3 - , (CF3SO2)2N - , (CF3CF2SO2)2N - , CF3(CF2)3SO3 - , (CF3SO2)3C - , CF3(CF2)2COO - The anion of the imidazolium salt is ClO4 - , (CF3SO2)2N - , CF3SO3- etc. are more preferable.
[0039] Examples of borates include those having one or more alkyl or aryl groups having about 1 to 18 carbon atoms (such as methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, phenyl, and xylyl groups) and containing alkali metal ions or alkaline earth metal ions such as lithium ions, sodium ions, potassium ions, and calcium ions.
[0040] From the viewpoint of low resistance, the content of the ionic conductive agent is preferably 0.1 parts by mass or more per 100 parts by mass of the component (a). More preferably, it is 0.3 parts by mass or more, and even more preferably, it is 0.5 parts by mass or more. Furthermore, from the viewpoint of easily suppressing bleeding of the ionic conductive agent, the content is preferably 5.0 parts by mass or less per 100 parts by mass of the component (a). More preferably, it is 3.0 parts by mass or less, and even more preferably, it is 2.0 parts by mass or less.
[0041] The piperidinyloxy radical compound functions as a retarder in crosslinking. The piperidinyloxy radical compound maintains an equilibrium state with the radicals generated by the thermal decomposition of the crosslinking agent. In the early stage of crosslinking, when the amount of radicals generated is relatively small, the piperidinyloxy radical compound maintains an equilibrium state with the generated radicals and suppresses the crosslinking reaction (delaying the crosslinking start time (T10)). On the other hand, the crosslinking rate can be increased by raising the crosslinking temperature. This allows only the crosslinking start time (T10) to be delayed, and the overall crosslinking rate (T90) is not delayed. By adjusting the crosslinking rate in this way, the molecular arrangement of the polymer is controlled. Since gaps are generated in the polymer that allow the ions of the ionic conductive agent to enter appropriately, the polar groups of the polymer can be appropriately coordinated to the ions of the ionic conductive agent. This suppresses excessive polarization of the ionic conductive agent even when an electrical load is applied by passing electricity. In addition, by delaying T10, the salt of the cyclic amidine compound and the like can be uniformly diffused into the rubber by thermal diffusion before the hardening of the rubber progresses. This allows the ionic conductive agent to be uniformly dispersed in the rubber, suppressing excessive polarization of the ionic conductive agent even when an electrical load is applied by passing a current through it. Note that T10 is the time (s) required to reach 10% of the maximum torque at the molding temperature (crosslinking temperature), and T90 is the time (s) required to reach 90% of the maximum torque at the molding temperature (crosslinking temperature).
[0042] The piperidinyloxy radical compound is a compound represented by the following general formula (1). [ka]
[0043] Examples of R1 to R4 include hydrogen, an alkyl group having 1 to 4 carbon atoms, etc. Examples of R5 include hydrogen, an alkyl group having 1 to 4 carbon atoms, an aryl group, an acetoxy group, a benzyloxy group, a carboxylic acid group, an acetamide group, and an aldehyde group.
[0044] Preferred examples of the piperidinyloxy radical compound include 2,2,6,6-tetramethylpiperidinyloxy radical, 4-hydroxy-2,2,6,6-tetramethylpiperidinyloxy radical, 4-benzoyloxy-2,2,6,6-tetramethylpiperidinyloxy radical, 4-acetamido-2,2,6,6-tetramethylpiperidinyloxy radical, etc. Among these, 4-hydroxy-2,2,6,6-tetramethylpiperidinyloxy radical, 4-benzoyloxy-2,2,6,6-tetramethylpiperidinyloxy radical, 4-acetamido-2,2,6,6-tetramethylpiperidinyloxy radical, etc. are more preferred from the viewpoints of the melting point being within the optimum range relative to the molding temperature of the rubber, radical scavenging ability, storage stability, and cost.
[0045] The phenol-based antioxidant exerts the same action and effect as the piperidinyloxy radical compound in the reaction system of the present invention. That is, it only delays the crosslinking start time (T10) and does not delay the overall crosslinking speed (T90). As the phenol-based antioxidant, a hindered phenol-based antioxidant can be used. In addition, monophenol-based, diphenol-based, triphenol-based, and polyphenol-based antioxidants can be used.
[0046] Hindered phenol antioxidants include 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-hexane-1,6-diylbis[3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5 -triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-methylphenol, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), 4,4',4''-[(2,4,6-tri)methylbenzene-1,3,5-triyl]tris(methylene)]tris(2,6-di-tert-butylphenol), and the like.
[0047] From the viewpoint of suitability in adjusting the crosslinking rate, the content of (d) is preferably 0.05 parts by mass or more relative to 100 parts by mass of component (a). More preferably, it is 0.1 parts by mass or more, and even more preferably, it is 0.2 parts by mass or more. Moreover, the content of (d) is preferably 3.0 parts by mass or less relative to 100 parts by mass of component (a). More preferably, it is 2.0 parts by mass or less, and even more preferably, it is 1.0 part by mass or less.
[0048] A cyclic amidine compound is a cyclic compound that contains an amidine structure in its structure. A salt of a cyclic amidine compound has an appropriate polarity that can coordinate with the ions (cations) of an ionic conductive agent. When the salt of a cyclic amidine compound coordinates with the ions of an ionic conductive agent, excessive polarization of the ionic conductive agent is suppressed even when an electric load is applied by passing a current through the cyclic amidine compound. The cyclic amidine compound effectively exerts the above-mentioned effects in the form of a salt.
[0049] As the cyclic amidine compound, from the viewpoint of availability, a bicyclic amidine compound is preferable. As the cyclic amidine compound, diazabicycloundecene (1,8-diazabicyclo(5.4.0)undecene-7) and diazabicyclononene (1,5-diazabicyclo(4.3.0)nonene-5) are mentioned. As the cyclic amidine compound, diazabicycloundecene is more preferable from the viewpoint of cation coordination ability, storage stability, etc.
[0050] Examples of the salt of the cyclic amidine compound include naphthoic acid salts of the cyclic amidine compound, phenolic resin salts of the cyclic amidine compound, aliphatic carboxylates, phenol salts, borate salts, etc. As the salt of the cyclic amidine compound, naphthoic acid salts of the cyclic amidine compound are more preferable because they cause a small increase in resistance due to polarization of the ion conductive agent during current-carrying durability.
[0051] The thiophthalimide compound is a compound containing a thiophthalimide structure in its structure. In the reaction system of the present invention, the thiophthalimide compound exerts the same action and effect as the salt of the cyclic amidine compound. That is, the thiophthalimide compound has a suitable polarity that can be coordinated to the ions of the ionic conductive agent, and by coordinating to the ions of the ionic conductive agent, excessive polarization of the ionic conductive agent is suppressed even when an electric load is applied by passing a current. Examples of the thiophthalimide compound include N-cyclohexylthiophthalimide, N-trifluoromethylthiophthalimide, N-phenylthiophthalimide, and N,N'-thiodiphthalimide.
[0052] The content of (e) is preferably 0.1 parts by mass or more per 100 parts by mass of component (a) from the viewpoint of being excellent in the effect of suppressing excessive polarization of the ion conductive agent even when an electrical load is applied by passing a current. More preferably, it is 0.5 parts by mass or more, and even more preferably, it is 1.0 part by mass or more. Moreover, from the viewpoint of suppressing bleeding of (e), the content is preferably 5.0 parts by mass or less per 100 parts by mass of component (a). More preferably, it is 4.0 parts by mass or less, and even more preferably, it is 3.0 parts by mass or less.
[0053] The rubber composition may contain other additives as necessary, such as electronic conductive agents, lubricants, antioxidants, light stabilizers, viscosity modifiers, processing aids, flame retardants, plasticizers, fillers, dispersants, pigments, and mold release agents.
[0054] Examples of the electronic conductive agent include carbon black, graphite, conductive titanium oxide, conductive zinc oxide, and conductive tin oxide.
[0055] The rubber composition may further contain carbon black. Carbon black can adsorb cations of the ionic conductive agent, thereby suppressing bleeding of the ionic conductive agent. Carbon black having a specific surface area within a specific range can be preferably used. The larger the specific surface area of carbon black, the easier it is to adsorb cations of the ionic conductive agent. On the other hand, the larger the specific surface area, the more likely it is that carbon black will aggregate, and the more likely the conductivity will decrease. Therefore, in order to balance the effect of suppressing bleeding of the ionic conductive agent and the effect of suppressing a decrease in conductivity, the specific surface area of carbon black should be within a range of 40 m. 2 / g or more 300m 2 / g or less. More preferably, it is 42m 2 / g or more 240m 2 The specific surface area of carbon black can be measured by a nitrogen adsorption method.
[0056] The content of carbon black is preferably 5 parts by mass or more and 40 parts by mass or less, and more preferably 10 parts by mass or more and 30 parts by mass or less, per 100 parts by mass of component (a), taking into consideration the hardness and electrical conductivity of the elastic layer 14.
[0057] The thickness of the elastic layer 14 is not particularly limited, but is preferably within the range of 0.1 to 10 mm, more preferably within the range of 0.5 to 5 mm, and even more preferably within the range of 1 to 3 mm.
[0058] The volume resistivity of the elastic layer 14 is not particularly limited, but is preferably 102 ~10 10 Ω cm, more preferably 10 3 ~10 9 Ω cm, more preferably 10 4 ~10 8 It is in the range of Ω·cm.
[0059] The surface layer 16 can function as a protective layer for the roll surface. The surface layer 16 preferably contains, as a main material, a polymer component such as polyamide, polyurethane, acrylic resin, alkyd resin, phenolic resin, fluororesin, silicone resin, or modified products thereof. Examples of the modified group in the modified product include an N-methoxymethyl group, a silicone group, and a fluorine group. These polymer components may be contained alone as the surface layer material, or may be contained in combination of two or more types. The polymer component of the surface layer 16 may be crosslinked.
[0060] To impart electrical conductivity to the surface layer 16, a conductive agent such as carbon black, graphite, conductive titanium oxide, conductive zinc oxide, conductive tin oxide, or an ionic conductive agent (quaternary ammonium salt, borate, surfactant, etc.) may be appropriately added. In addition, various additives may be appropriately added as necessary. In addition, to ensure surface roughness, roughness-forming particles may be added.
[0061] The roughness-forming particles form surface irregularities on the surface layer 16. Examples of the roughness-forming particles include resin particles and silica particles. Examples of the resin particles include urethane particles, silicone particles, and acrylic particles. The average particle diameter of the roughness-forming particles is preferably within the range of 3 to 50 μm. The average particle diameter of the roughness-forming particles can be calculated from the median diameter using a laser diffraction particle size distribution measuring device.
[0062] The thickness of the surface layer 16 is not particularly limited, but is preferably in the range of 0.01 to 100 μm, more preferably in the range of 0.1 to 20 μm, and further preferably in the range of 0.3 to 10 μm.7 ~10 12 Ω cm, more preferably 10 8 ~10 11 Ω cm, more preferably 10 9 ~10 10 It is in the range of Ω·cm.
[0063] The electrostatic charge roll 10 can be manufactured, for example, as follows. First, the shaft 12 is coaxially placed in the hollow portion of a roll molding die, and a rubber composition is injected and heated / cured, and then the die is demolded or the rubber composition is extruded onto the surface of the shaft 12 to form the elastic layer 14 on the outer periphery of the shaft 12. Next, a surface layer forming composition is applied to the outer periphery of the formed elastic layer 14, and ultraviolet light is irradiated or heat treatment is performed as necessary to form the surface layer 16. In this manner, the electrostatic charge roll 10 can be manufactured.
[0064] The surface layer forming composition contains the above-mentioned main material, the conductive agent, and other additives that are contained as necessary. Examples of other additives include crosslinking agents for polymer components, leveling agents, and surface modifiers. From the viewpoint of adjusting the viscosity, the surface layer forming composition may contain a solvent such as an organic solvent such as methyl ethyl ketone, toluene, acetone, ethyl acetate, butyl acetate, methyl isobutyl ketone (MIBK), THF, or DMF, or a water-soluble solvent such as methanol or ethanol. As the coating method, various coating methods such as a roll coating method, a dipping method, and a spray coating method can be applied.
[0065] According to the charging roll 10 having the above configuration, since the elastic layer 14 is composed of a crosslinked rubber composition containing the above (a) to (e), the resistance increase during the current-carrying durability and the bleeding of the ionic conductive agent are suppressed. This is presumed to be due to the following mechanism. That is, the salt of the cyclic amidine compound or the thiophthalimide compound coordinates with the ions of the ionic conductive agent, so that excessive polarization of the ionic conductive agent is suppressed even when an electric load is applied by current-carrying. In addition, the piperidinyloxy radical compound or the phenol-based antioxidant slows down only the crosslinking start time (T10) during crosslinking of the hydrin rubber or nitrile rubber, and does not delay the overall crosslinking speed (T90). By adjusting the crosslinking speed in this way, the molecular arrangement of the polymer is controlled. Since gaps are generated in the polymer that allow the ions of the ionic conductive agent to enter appropriately, the polar groups of the polymer can be appropriately coordinated with the ions of the ionic conductive agent. As a result, excessive polarization of the ionic conductive agent is suppressed even when an electric load is applied by current-carrying. In addition, by delaying T10, the salt of the cyclic amidine compound and the like can be uniformly diffused in the rubber by thermal diffusion before the hardening of the rubber progresses. As a result, the ionic conductive agent is uniformly dispersed in the rubber, so that excessive polarization of the ionic conductive agent is suppressed even when an electrical load is applied by passing an electric current. As a result, the increase in resistance during the durability of the electric current is suppressed. In addition, since excessive polarization of the ionic conductive agent is not suppressed by increasing the amount of the ionic conductive agent, bleeding of the ionic conductive agent is also suppressed. In addition, by slowing down only the crosslinking start time (T10) and not delaying the overall crosslinking speed (T90), gaps are created in the polymer through which the ions of the ionic conductive agent can enter, and the polar groups of the polymer are appropriately coordinated to the ions of the ionic conductive agent, making it more difficult for the ionic conductive agent to bleed, so that bleeding of the ionic conductive agent can be suppressed even if the amount of the ionic conductive agent is increased.
[0066] When the ionic conductive agent is an ammonium, phosphonium, or imidazolium type, the polar group of the rubber component (a) is easily coordinated to the cation of the ionic conductive agent, and excessive polarization of the ionic conductive agent is easily suppressed even during electrical durability, which is particularly effective in suppressing an increase in resistance during electrical durability. Also, the salt of the cyclic amidine compound or the thiophthalimide compound (e) is easily coordinated to the cation of the ionic conductive agent, and excessive polarization of the ionic conductive agent is easily suppressed even during electrical durability, which is particularly effective in suppressing an increase in resistance during electrical durability. Also, it is easy to achieve low resistance.
[0067] When the ionic conductive agent contains a sulfonate anion having a fluorine atom or a bis(sulfonyl)imide anion having a fluorine atom, the anion itself has a low basicity due to the large amount of fluorine groups contained in the structure, and forms a relatively weak ionic bond with the cation. Therefore, these ionic conductive agents are easily dissociated into ions in the rubber (a), and are easy to achieve low resistance. In addition, all of these anions are hydrophobic, and have low hygroscopicity even in a high humidity environment. Therefore, they are excellent in the effect of suppressing fluctuations in electrical resistance due to environmental changes. And, ionic conductive agents containing perchlorate anions are easy to achieve low resistance. EXAMPLES
[0068] The present invention will be described in detail below using examples and comparative examples.
[0069] (Experimental Example 1) <Preparation of Rubber Composition> A rubber composition was prepared by mixing and stirring 100 parts by mass of hydrin rubber (ECO), 3 parts by mass of a peroxide crosslinking agent (Peroximon F40) (1.2 parts by weight calculated as the amount of the original material), 0.2 parts by mass of a piperidinyloxy radical compound (4-hydroxyTEMPO radical), 5 parts by mass of an acid acceptor, 1 part by mass of an ion conductive agent, and 0.1 part by mass of a salt of a cyclic amidine compound (naphthoic acid salt of diazabicycloundecene) with a stirrer.
[0070] <Formation of Elastic Layer> A core bar (diameter 6 mm) was set in a molding die, and the above rubber composition was injected at 120° C. and heated at 175° C. for 30 minutes to crosslink the rubber composition. After that, the product was cooled and demolded to form an elastic layer having a thickness of 2 mm on the outer periphery of the core bar.
[0071] <Surface formation> A surface layer forming composition was prepared by mixing 100 parts by mass of N-methoxymethylated nylon ("EF30T" manufactured by Nagase ChemteX), 60 parts by mass of conductive tin oxide ("S-2000" manufactured by Mitsubishi Materials), 1 part by mass of citric acid, and 300 parts by mass of methanol. Next, the surface layer forming composition was roll-coated on the surface of the elastic layer and heated at 120°C for 50 minutes to form a surface layer having a thickness of 10 μm on the outer periphery of the elastic layer. In this way, the charging roll according to Example 1 was produced.
[0072] (Experimental Example 2) A charging roll was produced in the same manner as in Experimental Example 1, except that in the preparation of the rubber composition, the compounded amount of the salt of the cyclic amidine compound was changed.
[0073] (Experimental Examples 3-4) A charging roll was produced in the same manner as in Experimental Example 1, except that in the preparation of the rubber composition, the compounded amounts of the salt of the cyclic amidine compound and the piperidinyloxy radical compound were changed.
[0074] (Experimental Examples 5-6) A charging roll was produced in the same manner as in Experimental Example 1, except that in the preparation of the rubber composition, the type and amount of the salt of the cyclic amidine compound were changed.
[0075] (Experimental Example 7) A charging roll was produced in the same manner as in Experimental Example 1, except that in the preparation of the rubber composition, a thiophthalimide compound was used instead of the salt of the cyclic amidine compound, and the compounding amount was changed.
[0076] (Experimental Example 8) A charging roll was produced in the same manner as in Experimental Example 1, except that in the preparation of the rubber composition, nitrile rubber (NBR) was used instead of hydrin rubber (ECO) and the compounded amount of the cyclic amidine compound was changed.
[0077] (Experimental Example 9) In preparing the rubber composition, a phenolic antioxidant was used instead of the piperidinyloxy radical compound, the amount of the antioxidant was changed, and further, the amount of the cyclic amidine compound was changed. In the same manner as in Experimental Example 1, except for this, an electrostatic charging roll was produced.
[0078] (Experimental Example 10) A charging roll was produced in the same manner as in Experimental Example 1, except that in the preparation of the rubber composition, the compounded amount of the salt of the cyclic amidine compound was changed, and further, the compounded amount of the ionic conductive agent was changed.
[0079] (Experimental Examples 11-12) A charging roll was produced in the same manner as in Experimental Example 10, except that in the preparation of the rubber composition, the type of ionic conductive agent was changed.
[0080] (Experimental Example 13) A charging roll was produced in the same manner as in Experimental Example 1, except that in the preparation of the rubber composition, the compounded amount of the salt of the cyclic amidine compound was changed and carbon black was further compounded.
[0081] (Experimental Example 21) A charging roll was produced in the same manner as in Experimental Example 1, except that in the preparation of the rubber composition, the salt of the cyclic amidine compound and the piperidinyloxy radical compound were not mixed.
[0082] (Experimental Example 22) A charging roll was produced in the same manner as in Experimental Example 21, except that the amount of the ionic conductive agent was increased in the preparation of the rubber composition.
[0083] (Experimental Examples 23-26) A charging roll was produced in the same manner as in Experimental Examples 4 to 7, except that in the preparation of the rubber composition, no piperidinyloxy radical compound was added.
[0084] (Experimental Example 27) A charging roll was produced in the same manner as in Experimental Example 4, except that in the preparation of the rubber composition, the salt of the cyclic amidine compound was not mixed.
[0085] (Experimental Example 28) A charging roll was produced in the same manner as in Experimental Example 9, except that in the preparation of the rubber composition, the salt of the cyclic amidine compound was not mixed, and further, the amount of the phenol-based antioxidant mixed was changed.
[0086] As materials for the elastic layer forming composition, the following materials were prepared. Hydrin rubber (ECO): Osaka Soda's "Epicromer CG102" Nitrile rubber (NBR): "Nipol DN3335" manufactured by Nippon Zeon Crosslinking agent: NOF's "Peroximon F40" Diazabicycloundecene salts <1> : 3-Hydroxy-2-naphthoic acid salt of 1,8-diazabicyclo(5.4.0)undecene-7 Diazabicycloundecene salts <2> : Phenolic resin salt of 1,8-diazabicyclo(5.4.0)undecene-7 Diazabicyclononene salt: phenolic resin salt of 1,5-diazabicyclo(4.3.0)nonene-5 Thiophthalimide compounds: N-cyclohexylthiophthalimide ·Piperidinyloxy radical compound: 4-hydroxy-2,2,6,6-tetramethylpiperidinyloxy radical Phenolic antioxidant: 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate Acid acceptor: Kyowa Chemical Industry's "DHT-4A" ·Ionic conductive agent <1> : "Tetrabutylammonium triflate" manufactured by Tokyo Chemical Industry Co., Ltd. ·Ionic conductive agent <2> : The following phosphonium salts (synthetic products) ·Ionic conductive agent <3> : 1-Ethyl-3-methylimidazolium bromide manufactured by Shikoku Chemical Industry Co., Ltd. Carbon black: Tokai Carbon's "Seast 9" (specific surface area 142 m 2 / g)
[0087] <Synthesis of phosphonium salts> Tri-n-butyldodecylphosphonium bromide and bis(trifluoromethanesulfonyl)imidic acid were added to a mixture of methylene chloride and ion-exchanged water (1:1), and the mixture was stirred at room temperature for 4 hours, after which tri-n-butyldodecylphosphonium bis(trifluoromethanesulfonyl)imide was obtained from the organic layer.
[0088] The produced charging roll was evaluated for resistance change during energization and bleeding of the ion conductive agent.
[0089] <Method for evaluating change in electrical resistance> A load of 700 g was applied to each end of the charging roll on a φ30 mm metal drum, the metal drum was rotated at 90 rpm, and a current test was performed so that the accumulated current was 20,000 μA·h. The resistance values before and after the test were obtained, and the resistance change was calculated in digits. A resistance change of less than 0.7 digits was rated "A," a resistance change of 0.7 to 1.0 digits was rated "B," and a resistance change of 1.0 digit or more was rated "C."
[0090] <Bleeding evaluation method> The charging roll was left in a humid and hot environment at 40°C for 30 days, and then the surface of the charging roll was observed to see if there was any bleeding. If no bleeding was observed, it was rated "A", and if bleeding was observed, it was rated "B".
[0091] [Table 1]
[0092] [Table 2]
[0093] In the experimental examples 1 to 13, in the preparation of the rubber composition, one or more selected from hydrin rubber and nitrile rubber, one or more selected from crosslinking agent, ionic conductive agent, piperidinyloxy radical compound and phenolic antioxidant, one or more selected from salt of cyclic amidine compound and thiophthalimide compound are blended, and the resistance increase due to polarization of the ionic conductive agent is small during the electric current durability. Also, bleeding of the ionic conductive agent is not observed.
[0094] In Experimental Example 21, the rubber composition was prepared without the salt of a cyclic amidine compound, the thiophthalimide compound, the piperidinyloxy radical compound, and the phenol-based antioxidant, and the resistance increase due to the polarization of the ionic conductive agent was large during the electric current durability test. In Experimental Example 22, the resistance increase during the electric current durability test was suppressed by increasing the amount of the ionic conductive agent, but the bleed of the ionic conductive agent was observed. In Experimental Examples 23 to 26, the rubber composition was prepared without the piperidinyloxy radical compound and the phenol-based antioxidant, and the resistance increase due to the polarization of the ionic conductive agent was somewhat large during the electric current durability test. In Experimental Examples 27 to 28, the rubber composition was prepared without the salt of a cyclic amidine compound and the thiophthalimide compound, and the resistance increase due to the polarization of the ionic conductive agent was large during the electric current durability test.
[0095] Although the embodiments and examples of the present invention have been described above, the present invention is not limited to the above-mentioned embodiments and examples, and various modifications are possible without departing from the spirit and scope of the present invention. [Explanation of symbols]
[0096] 10. Charging roll 12 Axial body 14 Elastic layer 16 Surface layer
Claims
1. A shaft body and an elastic layer formed on an outer circumferential surface of the shaft body, The charging roll for electrophotographic equipment, wherein the elastic layer is a crosslinked product of a rubber composition containing the following (a) to (e): (a) One or more rubbers selected from hydrin rubber and nitrile rubber (b) Crosslinking Agent (c) Ionic Conductive Agent (d) One or more selected from piperidinyloxy radical compounds (e) one or more selected from salts of cyclic amidine compounds and thiophthalimide compounds
2. 2. The charging roll for an electrophotographic apparatus according to claim 1, wherein said (e) is a naphthoic acid salt of a cyclic amidine compound.
3. 2. The charging roll for an electrophotographic apparatus according to claim 1, wherein said (e) is N-cyclohexylthiophthalimide.
4. 3. The charging roll for an electrophotographic apparatus according to claim 1, wherein the (c) is an ammonium-based, phosphonium-based, or imidazolium-based ionic conductive agent.
5. 3. The charging roll for electrophotographic equipment according to claim 1, wherein the (c) is an ionic conductive agent containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion.
6. The rubber composition further has a specific surface area of 40 m 2 / g or more 300m 2 3. The charging roll for electrophotographic equipment according to claim 1, further comprising carbon black having a surface area of 0.1 to 0.2 g / g or less.
7. (e) is a naphthoic acid salt of a cyclic amidine compound or N-cyclohexylthiophthalimide; the (c) is an ammonium-based, phosphonium-based, or imidazolium-based ion-conducting agent containing a sulfonate anion having a fluorine atom, a bis(sulfonyl)imide anion having a fluorine atom, or a perchlorate anion; The rubber composition further has a specific surface area of 40 m 2 / g or more 300m 2 2. The charging roll for an electrophotographic device according to claim 1, comprising carbon black having a surface area of 0.1 to 0.5 μm / g or less.